2009
DOI: 10.1093/brain/awp148
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of hippocampal network activity is disrupted by neuroinflammation: rescue by memantine

Abstract: Understanding how the hippocampus processes episodic memory information during neuropathological conditions is important for treatment and prevention applications. Previous data have shown that during chronic neuroinflammation the expression of the plasticity related behaviourally-induced immediate early gene Arc is altered within the CA3 and the dentate gyrus; both of these hippocampal regions show a pronounced increase in activated microglia. Low doses of memantine, a low to moderate affinity open channel un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
80
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 38 publications
13
80
2
Order By: Relevance
“…For example, using essentially the identical procedures and environments used here and in Chawla et al (2005), Rosi et al (2009) found that, for both CA3 and CA1, X 2 /X 1 were very close to the expected values.…”
Section: Discussionsupporting
confidence: 55%
“…For example, using essentially the identical procedures and environments used here and in Chawla et al (2005), Rosi et al (2009) found that, for both CA3 and CA1, X 2 /X 1 were very close to the expected values.…”
Section: Discussionsupporting
confidence: 55%
“…2C) (P < 0.01). Microglia, the innate immune cells of the CNS, usually reside in the quiescent state; these cells are tightly regulated and, upon activation, release cytotoxic compounds that disrupt homeostatic processes and neuronal functions (24)(25)(26). Microglia are activated following surgery, changing their small cell bodies and thin, long, ramified pseudopodia into an amoeboid morphology, with enlargement of the cell body (features described as microgliosis).…”
Section: Anti-tnf Prophylaxis Prevents Neuroinflammation and Cognitivementioning
confidence: 99%
“…There are reports that neuroinflammation affects the accuracy of information processing in the CA3 and CA1 hippocampal regions. Memantine treatment, which indirectly prevents pathological microglial activation during the development of the pathology, has been shown to partially normalize information processing in the hippocampus, suggesting that modulation of neuroinflammation may improve the cognitive function of patients with TLE [100].…”
Section: Dynamic Regulation Of the Inflammatory Reaction And Bbb Funcmentioning
confidence: 99%